Setor da panificação: principais riscos e fatores de risco laborais, doenças profissionais associadas e medidas de proteção recomendadas - Santos, Mónica (2018)
Introduction Professionals working in occupational health teams, even if not directly connected to the Bakery sector can receive workers with these employment history. The Bakery industry professionals are exposed to various risks / risk factors, some of which are poorly understood; in addition, most of the literature addresses specific partial risk, it is not easy to find a global perspective, in the context of Occupational Health. Methodology Question protocol: What are the main risk factors and risks for the Bakery industry professionals, as well as associated professionals diseases and recommended protective measures? A survey was carried out in December 2015, in the databases “CINALH plus with full text, Medline with full text, Database of Abstracts of Reviews of Effects, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, Cochrane Methodology Register, Nursing and Allied Health Collection: comprehensive, MedicLatina and Academic Search Complete. “ Content The main risks/ risk factors associated with the Bakery sector relate to the handling of loads, forced/ maintained postures and associated lesions; biological agents and allergens; chronobiological disruption; inadequate luminance; thermal discomfort (due to high temperatures and temperature differences); noise, vibrations and possible injuries associated with used machines. Conclusions The majority of workers in this professional sector is not aware of the importance or intensity of some risks, so they sometimes belittles that some collective or individual protection measures are not necessary. The main occupational diseases in this industry mentioned in the bibliography are asthma, hearing loss and possibly some musculoskeletal injuries. The main collective and individual protection measures outlined for this sector were not mentioned explicitly in any of the studies reviewed. Not only the data presented in this review resumes what the latest was published on occupational health in this sector (in Portuguese and using articles that addressed sketchy aspects and written in other languages), in order to provide easy access to this information from the professionals that begin in this sector; but also realized that the situation in Portugal is not sufficiently depicted, so it would be relevant motivate occupational health professionals working in the field (or that will work) to investigate relevant aspects of the issue, disseminating the findings obtained through the publication of articles.